2014
DOI: 10.1016/j.cub.2014.09.055
|View full text |Cite
|
Sign up to set email alerts
|

B. subtilis GS67 Protects C. elegans from Gram-Positive Pathogens via Fengycin-Mediated Microbial Antagonism

Abstract: Studies on Caenorhabditis elegans have provided detailed insight into host-pathogen interactions. Usually, the E. coli strain OP50 is used as food source for laboratory studies, but recent work has shown that a variety of bacteria have dramatic effects on C. elegans physiology, including immune responses. However, the mechanisms by which different bacteria impact worm resistance to pathogens are poorly understood. Although pathogen-specific immune priming is often discussed as a mechanism underlying such obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
(77 reference statements)
1
25
0
Order By: Relevance
“…While we keep more detailed analysis of individual genera and species for future studies investigating the interactions between nematodes and bacteria, we would like to point out that the family Enterobacteriaceae includes Escherichia coli , which is the most widely used food source of P. pacificus and C. elegans . Other bacterial families such as Bacillaceae , for which interactions with P. pacificus and C. elegans have been studied (Sinha et al ., ; Iatsenko et al ., ; Iatsenko et al ., ), were not found in high abundance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we keep more detailed analysis of individual genera and species for future studies investigating the interactions between nematodes and bacteria, we would like to point out that the family Enterobacteriaceae includes Escherichia coli , which is the most widely used food source of P. pacificus and C. elegans . Other bacterial families such as Bacillaceae , for which interactions with P. pacificus and C. elegans have been studied (Sinha et al ., ; Iatsenko et al ., ; Iatsenko et al ., ), were not found in high abundance.…”
Section: Resultsmentioning
confidence: 99%
“…Other bacterial families such as Bacillaceae, for which interactions with P. pacificus and C. elegans have been studied (Sinha et al, 2012;Iatsenko et al, 2014;Iatsenko et al, 2013), were not found in high abundance.…”
Section: The Microbiome Of Decaying Beetles Is Dominated By a Single mentioning
confidence: 99%
“…ESI/MS was applied to determine the molecular structures of all three main lipopeptides (Surfactins, iturins, and fengycins) (Pecci et al, 2010; Iatsenko et al, 2014). As one of the most important members of the lipopeptides family, the molecular structure of surfactins has the following characteristics: (1) a fatty acid chain linked with a seven-amino acids-peptide via its β-hydroxy; (2) the C-terminal amino acid residues of peptide that turns to cyclic compound; (3) positions 3 and 6 of N-terminal side of the peptide are Leu, position 5 is Asp, and position 2, 4, and 7 are non-determinate, generally Val, Leu or Ile (Horowitz and Griffin, 1991; Jacques, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, C. elegans fed B. subtilis GS67 (GS67) showed strong resistance to the pathogenic effects of B. thuringiensis DB27 (DB27) [36]. GS67 can inhibits growth of DB27 directly and also reduce the colonization of DB27 in C. elegans intestine.…”
Section: Bacterial Effects On C Elegans Life History Traits Pathogementioning
confidence: 99%